IMPACT OF TRANSPORTATION COSTS AND INFRASTRUCTURE QUALITY ON INDONESIAN IMPORTS - Tanti Novianti; Yusman Syaukat; Mangara Tambunan; Pantjar Simatupang (Economic Journal of Emerging Markets, 2013)
AbstractThis article investigates the impact of sea and air transportation cost, as well as infrastructure quality, to Indonesia’s import. Employing a panel regression model to seek for the answer, the paper find that cost reduction for sea transportation has greater impact on the Indonesia’s import volume compared to the air transportation. This paper also finds that Indonesia’s infrastructure quality has a significant positive impact on Indonesia’s import. The quality of ports, roads, and Linear Connectivity International Shipping (LSCI) are significant factors affecting import volume by sea transportation mode. Meanwhile, import volume by air transportation is significantly affected by the quality of the roads and airports.Keyword: Transportation costs, sea and air transportation infastructure qualities, volume of importJEL classification numbers: D24, H54, F13AbstrakPaper ini menyelidiki pengaruh biaya transportasi laut dan udara dan kualitas infrastruktur erhadap impor Indonesia. Dengan menggunakan model regresi data panel, paper ini menemukan bahwa koefisien biaya transportasi untuk impor menggunakan transportasi laut lebih besar dibandingkan melalui udara. Dengan kata lain, turunnya biaya transportasi laut memiliki dampak yang lebih besar pada volume impor Indonesia dibandingkan melalui transportasi udara. Kualitas infrastruktur Indonesia memiliki dampak positif yang signifikan terhadap impor. Kualitas pelabuhan, jalan, dan Linear Connectivity International Shipping (LSCI) merupakan faktor penting yang dapat memengaruhi impor Indonesia melalui moda transportasi laut. Sementara itu, volume impor melalui moda transportasi udara dipengaruhi signifikan oleh kualitas jalan dan bandara udara. Kata kunci: Biaya transportasi, kualitas infrastruktur laut dan udara, volume impor JEL classification numbers: D24, H54, F13